Karyotypic abnormalities and molecular analysis of Y chromosome microdeletion in Iranian Azeri Turkish population infertile men. (3rd March 2020) - Akbarzadeh Khiavi, Mostafa; Jalili, Akbar; Safary, Azam; Gharedaghchi, Ziba; Mirinezhad, Seyed Kazem; Mehdizadeh, Amir; Rahmani, Seyyed Ali
ABSTRACT: Infertility is one of the major health-threatening problems in communities which may lead to psychological problems among couples. Y chromosome abnormalities and microdeletions have recently been considered as one of the male infertility factors. The aim of this study was to evaluate different chromosomal disorders and azoospermia factor b (AZFb), AZFc and AZFd microdeletions in idiopathic non-obstructive oligo or azoospermia infertile men. One hundred infertile (78 azoospermia and 22 oligospermia) and 100 fertile men were included in this study. Luteinizing hormone (LH) and follicle stimulating hormone (FSH) levels were evaluated by electrochemiluminescence. Karyotyping was performed according to standard methods and interpreted using the International System for Human Cytogenetic Nomenclature (ISHCN) recommendation. For Y chromosome microdeletion analysis, a multiplex polymerase chain reaction (PCR) was performed using STS primers. Higher FSH (24.32 ± 15.32 versus 8.02 ± 3.37, p < 0.0001) and LH (14.97 ± 8.26 versus 5.42 ± 2.73, p < 0.0001) were observed in infertile patients compared to their fertile counterpart. Additionally, 14% of infertile patients exhibited abnormal karyotype. The frequency of Y chromosome microdeletions in azoospermic and oligospermic patients was 32.05% (25/78) and 0% (0/22), respectively. Additionally, in azoospermic patients, the highest microdeletion frequency was related to the AZFc region (80%). Our data indicate the presence of chromosomal changes in the most infertile men, suggesting karyotype and molecular analysis of Y chromosome microdeletions for genetic counseling before assisted reproduction. Abbreviations: ART: assisted reproductive technology; AZF: azoospermia factor; DAZ: deleted in azoospermia; FCS: fetal calf serum; FSH: follicle stimulating hormone; LH: luteinizing hormone; PCR: polymerase chain reaction; SRY: sex-determining region Y; STS: sequence-tagged sites